South African anthropometric dimensions for the design of an ergonomic office chair - Korte, Janice (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2013)
Office chairs are becoming a modern status symbol in the workplace. Many individuals are seated on office chairs for most of the working day. As a result of using poorly designed chairs injury and discomfort are frequently experienced, most particularly lower back pain. Correct design of chairs is imperative, and must be user-centered. The aim of this investigation has been to gather anthropometric dimensions characteristic of the South African population, as this information has not been widely assimilated to date. Once collated, this information could be used in the design of an ergonomically correct office chair, suitable for the unique characteristics of the South African working population. Anthropometric dimensions were collected from 683 South Africans (comprising 448 South African females and 235 South African males) from pre-selected companies in major centres in South Africa (Johannesburg, Pietermaritzburg, Durban, East London, Grahamstown, Port Elizabeth and Cape Town). Measurements included participants' personal information (age, sex, home language and ethnic group), basic anthropometric measures (stature, shoulder height, mass, and waist and hip circumference) as well as specific measures of fit of the individual to the specially designed, adjustable chair. Of the 448 females, 317 were Black females, 77 were White females, 35 were Coloured females and 19 were Indian/Asian females. Of the 235 males, 112 were Black males, 79 were White males, 26 were Coloured males and 18 were Indian/Asian males. Office chair dimensions for each ethnic group were represented and differences were noted. A comparison between a current office chair's dimensions and the South African sample office chair's dimensions indicated modifications that would need to be constructed to suit the South African sample. The conventional office chair is still the most widely accepted office chair due to its stability and support structures that maintain the correct sitting posture of the user. An ergonomic office chair needs to incorporate anthropometric dimensions worldwide.
Keywords: Design -- Human factors; Office chairs; Chair design; Human engineering; Sitting position